Membangun Identitas Digital UMKM Kecantikan: Studi Perancangan Website The Ed Salon Padang - Vania Azzahra; Irhan Fernando; Azzahra Triana Putri; Zulfitri Yani; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The beauty and hair care industry in Indonesia is growing rapidly, especially small and medium enterprises (SMEs) in the salon sector. However, many SMEs still lack a digital identity and rely on conventional marketing methods without utilizing digital platforms. This study aimed to build a digital identity for The Ed Salon Padang, a beauty salon established in 1993 and operating in Padang, Bukittinggi, and Payakumbuh, through the design of a professional website profile. The method applied included three phases: wireframe design, website development using the SITE123 platform, and usability testing on multiple devices. The resulting website features the salon's profile, service list, photo gallery, and a WhatsApp reservation link, forming a coherent digital identity that represents the salon's brand. The outcome shows that building a digital identity through a website can expand customer reach, strengthen brand recognition, and support sustainable business promotion for SMEs.